Feasibilities and effectiveness of web-based psycho-educational: a pilot study at universities students - Kadek Suranata (Indonesian Institute for Counseling, Education and Therapy (IICET), 2019)
This pilot study aims to determine the feasibilites and effectiveness of web-based resilience programs at university students. This study conducted by the one group pretest posttest experimental design. The study participants were 15 university students at Universitas Pendidikan Ganesha Singaraja, Bali. The 14 items of Indonesian version resilience scale and the Health- Promoting Lifestyle Profile (HPLP II) administrated to evaluated the eefect of the program. The open questioner of acceptablity and feasibies used to evaluate the feasibility of the program based on students' perception, and veryvication by interview. The paired sample t-tes by JASP Versi 0.10.0 performed to analisys the data. The feasibilites program based on student perception is narated. The results of this study indicate that: (1) the programs are effective to improve student healt and life style and resilience, and (2) the program achieve high acceptance and feasibility students. The results of the study have implications for the e-counseling methods used in university